Sosio-Teologis: Dialektika Budaya Mengenai Inkarnasional Pelayanan Kristus dalam Kitab Injil - Bara Izzat Wiwah Handaru (Voice, 2021)
The principle of the Incarnation is that the word became flesh or became flesh, and the incarnation was done “in the midst of men” or “among men” (John 1:14). The Gospel writers saw Jesus as a human being who had a real human experience. The incarnation is a form of God's communication with humans in the world. The mission of the incarnation becomes God's work of salvation for mankind through the birth, ministry, suffering, death, resurrection and ascension of Christ. The incarnation became the pattern of God's mission, namely when the Father sent His Son to become man and live in the world. So that the Incarnation of Christ becomes the right model for the church in carrying out the preaching of the Gospel. It is undeniable that socio-cultural becomes a challenge for the church in carrying out its mission. Because it is still found that syncretism often occurs in the church. Therefore, the purpose of this research is how the church has the right model of service and applies it in ministry, especially in the context of the Indonesian nation which has a pluralistic socio-cultural environment. The incarnation mission has the relational concept "As God has sent me, so I send you".